Newer glucose-lowering drugs at discharge from cardiology hospitalization department: safetyness, effectiveness and mortality reduction. (25th November 2020) - Rozado Castano, J; Garcia Iglesias, D; Junco, A; Soroa, M; Barja, N; Alvarez, R; Adeba, A; Vigil-Escalera, M; Capin, E; Fidalgo, A; Martin, M; Calvo, D; et al.
Abstract: Background: In recent years, the paradigm of glycemic treatment has changed due to the cardiovascular impact of newer glucose-lowering drugs (GLD) (sodium-glucosa cotransporter 2 inhibitor (SGLT2i) and GLP-1 receptor agonist (GLP1a)). The cardiological patient with type 2 diabetes (2DM) is a very high cardiovascular risk patient in which the benefit of these therapies is greater. However, to date, different studies have demonstrated the efficacy and safety of newer GLD only in the outpatient setting. So its impact when they are initiated to discharge after a cardiovascular event is unknown. Objective: To evaluate the efficacy and safety of the onset of these newer GLD in 2DM patients at discharge from cardiology hospitalization. And to compare mortality and readmissions among patients treated with or without newer GLD. Methods: Prospective, it includes patients admitted to cardiology at a 3er level hospital between April/2018 and February/2019 with a history of 2DM or diagnosed with 2DM during hospitalization. They were followed at 6, 12 and 18 months. The evolution of anthropometric parameters, glycemic profile, renal function and blood pressure were analyzed; renal events, readmissions, mortality and combined clinical outcome (mortality or readmission) were collected during follow-up. Quantitative variables are expressed in mean/SD and categorical variables in number of patients (%). For the comparison between the parameters at discharge and thefollow-up, a T student was used for paired data. Survival analysis by K-M was performed crude and adjusted data by propensity score matching (PSM). Results: Population: Diagnoses at discharge: Acute coronary syndrome 66 (64%), Heart failure 22 (21%), Arrhythmias 16 (15%). 104 diabetic patients, 39 of them (38%) were treated on discharge with newer GLD. 35 Patients with SGLT2i without GLP1a, 3 patients with SGLT2i and GLP1a and 1 patient with GLP1a without SGLT2i. The mean follow-up was 16±2 months. Regarding the subgroup of patients with newer GLD: mean age was 65±21 y, male 26 (67%). A significant decrease was observed in glycated hemoglobin (7.6 to 6.9%, p=0.04) and weight (81 to 78 kg, p<0.01) without significant changes in blood pressure or glomerular filtration rate (GFR). Only 1 patient presented deterioration of their GFR that forced the transient suspension of newer GLD. 10 deaths were registered in the classical GLD group (15%) and none in the newer GLD group (HR 0.81 [0.71–0.92] p=0.002, Figure 1A, HR adjusted by PSM 0.9 [0.82–0.99], p=0.04), Figure 1B. The combined clinical outcome appeared in 38 patients (58%) in the the classical GLD group and in 9 (23%) in the newer GLD group (HR 0.70 [0.58–0.85] p<0.001, Figure 1C, PSM adjusted HR 0.75 [0.61–0.92], p=0.001), Figure 1D. Conclusion: The use of newer GLD at discharge from cardiology hospitalization reduce mortality and readmissions. Newer GLD were safe and showed significant reduction in weigth and glycated hemoglobin. Funding Acknowledgement: Type of funding source: None